Effects of the Incidence Density of Fever (IDF) on Patients Resuscitated From In-Hospital Cardiac Arrest: A Mediation Analysis - Hu, Yue; Guo, Yong; Wang, Xintao; Li, Yi; Sun, Dawei; Cui, Derong (Frontiers in Medicine, 2020)
Objective: The aim of this research was to study the factors contributing to the survival rate of in-hospital cardiac arrest (IHCA) and to determine whether the incidence density of fever (IDF) acts as a mediator. Methods: The data of patients with IHCA who survived more than 48 hours were collected from 2011 to 2017. IDF was defined as the fever duration dividing the hospitalization duration, prolonged fever as lasting more than five days, and early fever as onset within the first two days of IHCA. Possible clinical variables associated with IDF were examined by linear regression. Possible clinical variables associated with survival rate were examined by univariate and multivariate analyses. IDF was investigated as a mediator of the indirect effects of the risk factors on survival. Results: In our retrospective study, the median IDF was 0, with an interquartile range from 0 to 0.42. Prolonged fever accounted for 16% (97/605) and early fever accounted for 17.2% (104/605). Linear regression results show that positive chest X-ray, central venous catheter and Glasgow Coma Score (GCS) ≤ 8 are related to the IDF; At the same time, IDF(OR: 0.36, 95% C.I., 0.13–0.97, P = 0.04), prolonged fever(adjusted OR = 0.13, 95% C.I., 0.06–0.29, P < 0.001), positive chest X-ray(OR: 0.67, 95% C.I., 0.46–0.98, P = 0.04), central venous catheter(OR: 0.54, 95% C.I., 0.34–0.89, P = 0.01)，endotracheal intubation(OR: 0.47, 95% C.I., 0.33–0.69, P < 0.001) are also related to the negative outcome of hospital discharge after adjustment. Additionally, the Positive chest X-ray had a 19% effect on survival outcome through IDF as a mediator, and the indirect effect of central venous catheter mediated by IDF accounted for 10%. Conclusions: A higher IDF, prolonged fever, a positive chest X-ray, the use of a central venous catheter and endotracheal intubation reduced the survival rate of patients, and the detrimental impacts of a positive chest X-ray and the use of a central venous catheter on the survival outcome were partially mediated by IDF.